2214. National Testing Assessment of Select Bacterial STIs During the COVID-19 Pandemic. (15th December 2022) - Fonseca, Giuiseppe A; Maier, Marissa; Keddem, Shimrit; Borgerding, Joleen; Lowy, Elliott; McFarland, Lorenzo; Comstock, Emily; Van Epps, Puja; Ohl, Michael; Hauser, Ronald; Ross, David; Beste, Lauren
Abstract: Background: Chlamydia, gonorrhea, and syphilis infections rose in the US for 6 consecutive years before the COVID-19 pandemic. Patterns of sexually transmitted infection (STI) testing during the COVID-19 pandemic have yet to be fully assessed. Methods: We performed a retrospective study of STI testing in the Veteran's Health Administration (VHA) healthcare system during each calendar year 2019-2021 using electronic health record data. We determined the number of chlamydia (CT) and gonorrhea (GC), and syphilis tests performed overall and in demographic groups defined by age, birth sex, self-reported race, region, and HIV status. Results: VHA performed 202, 503 CT tests, 201, 314 GC tests and 250, 790 syphilis tests in 2019, followed by a 23% and 25% decrease in 2020 for CT/GC and syphilis testing, respectively. We observed decreases among all subgroups defined by age, sex, race, and geography. Race groups with the biggest decreases in 2020 include Asian Americans (-28%) and Hawaiian and Pacific Islanders (-27%). By 2021, overall testing rates demonstrated a partial recovery to 89.8% of their 2019 levels. Testing rates in 2021 in rural/ highly rural residents remained 17% below baseline, compared with 10% for urban dwellers. Veterans living in the Northeast, South, or Midwest had the least recovery among geographic regions (16%, 11% and 11% below baseline, respectively). People with HIV experienced a decline in CT/GC testing of 15% but by the end of 2021 this had recovered to 1.9% below baseline. Women experienced both a steeper drop and a smaller recovery in CT and GC testing relative to men (Figure 1), except for women under age 25 (Figure 2). Figure 1 STI testing rates by CY and sex Figure 2 Percent change in STI testing rates versus 2019 Conclusion: After dramatic reductions in STI testing during the COVID-19 pandemic, rates returned to near-baseline levels nationally by 2021. Testing rates have lagged in some patient groups, most notably rural and highly rural populations, women, and Black and Asian American Veterans, placing them at risk for disparities in STI diagnosis, and therefore treatment. Testing rates in Veterans under age 25 years have reached or exceeded pre-pandemic levels. Disclosures: All Authors : No reported disclosures.